Multiple Influence Factor Sensitivity Analysis and Height Prediction of Water-Conducting Fracture Zone - Xiaobin Li; Quansheng Li; Xuhui Xu; Yongqiang Zhao; Peng Li (Geofluids)
To explore the influence law and sensitivity of various factors on the height of the water-conducting fracture zone, and further predict the development height of the water-conducting fracture zone, taking the field survey and collected actual measured data as the research foundation, establishing mathematical model, regression analysis, and field measurement were adopted comprehensively. Based on the Data Processing System (DPS), influence factors of the development height of the water-conducting fracture zone were analyzed. By introducing sensitivity coefficient, a sensitivity quantification mathematical model was established, and sensitivity ranking was obtained. The regression relationship between each factor and the height of the water-conducting fracture zone was obtained by single factor analysis. Based on this, the prediction formula was proposed and successfully used in the field practice. Results show that the sensitivity coefficient of mining thickness, ratio coefficient of hard rock lithology, mining depth, and length of working face was 0.75, 0.69, 0.66, and 0.58, respectively. The dispersion degree of working face length and mining depth was greater than that of ratio coefficient of hard rock lithology and mining thickness. To some extent, it also reflects that the sensitivity of working face length and mining depth to the height of the water-conducting fracture zone was the weakest, which was consistent with the previous conclusions. Using the multiple regression mathematical model, a nonlinear statistical relationship between the height of the water-conducting fracture zone and ratio coefficient of hard rock lithology, mining thickness, working face length, and mining depth was obtained. This research provides some scientific basis and guidance for safe and efficient underwater mining.